Sorafenib/Regorafenib and Lapatinib interact to kill CNS tumor cells - Hamed, Hossein A. (2015)
The present studies were to determine whether the multi-kinase inhibitor sorafenib or its derivative regorafenib interacted with the ERBB1/ERBB2 inhibitor lapatinib to kill CNS tumor cells. In multiple CNS tumor cell types sorafenib and lapatinib interacted in a greater than additive fashion to cause tumor cell death. Tumor cells lacking PTEN, and anoikis or lapatinib resistant cells were as sensitive to the drug combination as cells expressing PTEN or parental cells, respectively. Similar data were obtained using regorafenib. Treatment of brain cancer cells with [sorafenib + lapatinib] enhanced radiation toxicity. The drug combination increased the numbers of LC3-GFP vesicles; this correlated with a reduction in endogenous LC3II, and p62 and LAMP2 degradation. Knock down of Beclin1 or ATG5 significantly suppressed drug combination lethality. Expression of c-FLIP-s, BCL-XL or dominant negative caspase 9 reduced drug combination toxicity; knock down of FADD or CD95 was protective. Expression of both activated AKT and activated MEK1 or activated mTOR was required to strongly suppress drug combination lethality. As both lapatinib and sorafenib are FDA approved agents, our data argue for further determination as to whether lapatinib and sorafenib is a useful glioblastoma therapy.